Leaders and heroes of the nation - Fikfak, Jurij (Traditiones (Ljubljana), 2014)
This thematic issue of Traditiones is dedicated to heroes and national leaders, and is mainly compiled from papers presented at a conference in Ljubljana in December 2013. The publication of these papers in 2014 presents an opportunity to remember the hundredth anniversary of the beginning of the First World War and at the same time offers a framework for reflections on how individual leaders in Europe or on its margins influenced and guided the masses in times of peace and war, and in times of crisis and catastrophe.
Keywords: history; zgodovina; znamenite osebnosti; personalities; voditelji; national identity; anthropology; antropologija; narodna identiteta